Job satisfaction among Malaysian optometrists: are we in dilemma? - Ahmad, Norsham; Syukran Jamil, Fatimah Az-Zahra (2021)
Several studies had evaluated the job satisfaction level among healthcare workers, but there has not been any study that assessed job satisfaction of optometrists in different work environments. How satisfied are Malaysian optometrist with their workplace? What are the factors that influence job satisfaction amongst optometrists? This cross-sectional survey aims to clarify above questions. The questionnaire used is adapted from previous studies with some modification. Internal consistency reliability was determined prior to data collection. Cronbach’s alpha reliability coefficient value was 0.9, which shows good reliability. Data from 256 optometrists from different workplace were analysed. The overall level of job satisfaction among optometrists was in a moderate satisfaction range (mean:4.51±0.08). Workplace facilities were rated the highest among other facets (mean:4.71±0.08), whereas promotional opportunities were the lowest (mean: 4.21±0.09). The Kruskal-Wallis analysis showed significant differences in overall satisfaction in the different workplace, χ2(3, N = 256) = 11.309, p<0.05. Workplace facilities, χ2(3, N = 256) = 18.787, p<0.05, and recognition, χ2(3, N = 256) = 11.240, p<0.05, were found to statistically and significantly influence the job satisfaction among optometrists. Dunn’s post-hoc test with Bonferroni correction showed that hospital-based optometrists are significantly satisfied with their job (p<0.05), specifically on workplace facilities (p<0.05) and recognition (p<0.05). In conclusion, Malaysian optometrists were moderately satisfied with their job and hospital-based workplace could offer better job satisfaction as compared to others. In which this setting could provide sufficient facilities and better recognition.